Ties to the Territory and Peacebuilding in Land Restitution Processes. The Case of the Municipalities of La Unión and Carmen De Viboral in Colombia - Jose Camilo Botero Suaza; Manuel José Gómez Restrepo; Susana Valencia Cárdenas; Yolima Lezcano Pajon (Iberoamericana: Nordic Journal of Latin American and Caribbean Studies)
This article analyses the ties to the territory and peacebuilding processes in the rural populations of the municipalities of La Unión and El Carmen de Viboral in the region of eastern Antioquia, a territory heavily affected by the Colombian armed conflict. A qualitative methodology was employed under a historical-hermeneutic approach, using in-depth interviews, focus groups, and pedagogical workshops as data collection techniques. The information was analysed following the guidelines of grounded theory. Land restitution in the studied area is progressing slowly, in a fragmented and inequitable manner, affecting the rooting of the rural population to the land; however, the organizational processes shape practices of situated peace, as they are produced from the experience of subjects and collectives with the capacity for agency and transformation. This is a practice that generates knowledge on how peace is built in the territory. Resumen Este artículo analiza los vínculos con la tierra, y los procesos de construcción de paz en las poblaciones rurales de los municipios de La Unión y El Carmen de Viboral en el Oriente antioqueño, territorio fuertemente golpeado por el conflicto armado colombiano. Utilizamos una metodología cualitativa bajo un enfoque histórico-hermenéutico, empleamos como técnicas de recolección de información entrevistas a profundidad, y grupos focales. La información la analizamos siguiendo los lineamientos de la teoría fundamentada. La restitución de tierras en la zona estudiada avanza lenta, fragmentaria e inequitativamente afectando el arraigo de la población rural a la tierra, no obstante, los procesos organizativos configuran prácticas de la paz situada, en tanto es producida desde la experiencia de sujetos y colectivos con capacidad de agencia y transformación. Es una práctica que genera un saber sobre cómo se construye la paz en el territorio. Palabras Claves: Arraigo; restitución de tierras; construcción de paz; Oriente Antioqueño